(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—Quantum dots (QDs) are semiconductor nanocrystals with exceptional optical and electronic properties, making them highly attractive in biomedical research [1], [6]. Their tunable fluorescence, broad excitation, and high photostability have positioned them as promising tools for cancer diagnostics [3], [7]. This review explores QD applications in in vitro diagnostics (IVD), point-of-care testing (POCT), bioimaging, and signal amplification strategies. Furthermore, emerging trends, safety considerations, and translational challenges are discussed, providing a roadmap toward clinical application [12].